Unite me - Mafi, Tahereh (2014)
"Juliette will not stand alone. In a battle that will decide the fate of her world. In Destroy me, Warner, the ruthless leader of Sector 45, refuses to let her go. In Fracture me, Adam, Juliette's first love, will do anything to get her back."--Page 4 of cover.
Destroy me -- Fracture me -- Juliette's journal.
"The Shatter Me novellas with Juliette's Journal."--Cover.
Includes excerpt from Ignite me (13 pages).
Keywords: Ability -- Juvenile fiction; Dictatorship -- Juvenile fiction; Science fiction; Love stories; Dystopias